Xinjiang and China's rise in Central Asia, 1949-2009 : a history - Clarke, Michael, 1977- (Routledge contemporary China series, 2011)
This book provides an account of how Beijing's evolving integrationist policies in Xinjiang have influenced its foreign policy in Central Asia since the establishment of the People's Republic in 1949, and how the policy of integration is related to China's concern for security and to its pursuit of increased power and influence in Central Asia.